The magical reality of Nadia - Yūsuf, Bāsim, 1974-; Daly-Weir, Catherine (Scholastic Inc., 2021)
From Bassem Youssef, a.k.a. The Jon Stewart of the Arab World, comes a hilarious and heartfelt story about prejudice, friendship, empathy, and courage. Nadia loves fun facts. Here are a few about her: - She collects bobbleheads -- she has 77 so far. - She moved from Egypt to America when she was six years old. - The hippo amulet she wears is ancient...as in it's literally from ancient Egypt. - She's going to win the contest to design a new exhibit at the local museum. Because how cool would that be?! (Okay, so that last one isn't a fact just yet, but Nadia has plans to make it one.) But then a new kid shows up and teases Nadia about her Egyptian heritage. It's totally unexpected, and totally throws her off her game. And something else happens that Nadia can't explain: Her amulet starts glowing! She soon discovers that the hippo is holding a helpful -- and hilarious -- secret. Can she use it to confront the new kid and win the contest? From The Daily Show comedian Bassem Youssef and author Catherine Daly comes a humorous and heartfelt story about prejudice, friendship, empathy, and courage. Includes sections of black-and-white comics as well as lively black-and-white illustrations throughout.